Ultimate strength and fracture behaviour of cracked welded square hollow section T-joints - Yang, Zhengmao (2008)
Three full-scale cracked square hollow section (SHS) T-joints were tested, and an actual numerical model was proposed. Based on this model, an automatic mesh generation program is developed. The plastic collapse load of cracked SHS T-joints is derived and validated experimentally and numerically. Furthermore, Based on the J-integral approach the failure assessment diagrams (FADs) of the SHS T-joints are constructed and compared with the standard FADs. It is confirmed that the standard BS7910 (1999) Level 3A FAD is appropriated for determining limits of safe loading of cracked SHS T-joints under brace end axial loads provided the plastic collapse load is calculated using the conservative yield line formulae neglecting the influence of the welds and the chord wall thickness.